Perspective: The Environmental Implications of Oil Theft and Artisanal Refining in the Niger Delta Region - Moses, Obenade; Tami, Amangabara, Gordon (Asian Review of Environmental and Earth Sciences, 2014)
Illegal oil bunkering and artisanal refining are on the rise in various communities in the Niger Delta and worsen the ecological destruction and social conflict caused by the oil industry. This review examines the concept of oil theft and artisanal refining and their environmental implications and concluded that Oil theft and artisanal refining in the Niger Delta are massive and growing problems. It is estimated that between 200,000 and 300,000 barrels of oil is lost daily to theft, known in the country as illegal bunkering. The majority of the stolen crude oil is taken to large ocean-going tankers waiting offshore, which export the oil to refineries outside the country to the rest of the world. Stolen oil is also refined in makeshift individual facilities into low quality petroleum products. The authors conclude that while acknowledging the seeming social and economic advantages that artisanal refining brings to the host communities, and the argument that artisanal refining actually represents an opportunity which could be harnessed by the government to enhance economic and social opportunities in an environment of high unemployment and poverty, especially in the oil-producing areas of the country, the disadvantages far outweigh the seeming advantages both to the community and the environment at large.